The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1136/archdischild-2014-307297
|View full text |Cite
|
Sign up to set email alerts
|

Reducing hospital-acquired infections and improving the rational use of antibiotics in a developing country: an effectiveness study

Abstract: BackgroundPrevention of hospital-acquired infections (HAI) is central to providing safe and high quality healthcare. Transmission of infection between patients by health workers, and the irrational use of antibiotics have been identified as preventable aetiological factors for HAIs. Few studies have addressed this in developing countries.AimsTo implement a multifaceted infection control and antibiotic stewardship programme and evaluate its effectiveness on HAIs and antibiotic use.MethodsA before-and-after stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
115
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(127 citation statements)
references
References 22 publications
8
115
1
3
Order By: Relevance
“…4,6,[15][16][17][18] The great majority of children in our cohort had an underlying disease (93.3%), a proportion quite similar to previous data in pediatric ICUs. 19 Consistent with previous studies, BSIs represented the leading cause of pediatric HAIs, followed by LRTIs and urinary tract infections. 6,[16][17][18]20 These findings underline how children differ from adults in HAI distribution, emphasizing the need to target interventions focused on BSI prevention in neonates and children.…”
Section: Discussionsupporting
confidence: 75%
“…4,6,[15][16][17][18] The great majority of children in our cohort had an underlying disease (93.3%), a proportion quite similar to previous data in pediatric ICUs. 19 Consistent with previous studies, BSIs represented the leading cause of pediatric HAIs, followed by LRTIs and urinary tract infections. 6,[16][17][18]20 These findings underline how children differ from adults in HAI distribution, emphasizing the need to target interventions focused on BSI prevention in neonates and children.…”
Section: Discussionsupporting
confidence: 75%
“…Five studies reported on the reduction of antibiotic consumption [11][12][13][14][15] , seven reported on the reduction of broad spectrum/restricted antibiotic use 11,12,[15][16][17][18][19] , one reported on HAI reduction , 13 and one reported on reduction of bacterial resistance. 18 Two studies evaluated ASPs costs.…”
Section: Resultsmentioning
confidence: 99%
“…These differences may have been due to studying only children below 5 years of age or including adults. 4,7,8,9 Most of our subjects were < 1 year of age (25; 54.3%) or 1 -< 5 years old (18; 39.1%), with a 1:1 ratio of males to females. Pneumonia was found to be the main cause of morbidity and mortality in children below 5 years by Latumahina et al and the Indonesian Ministry of Health.…”
Section: Resultsmentioning
confidence: 99%